Macroeconomic Trends in the Kim Jong-un Era: Continuation or Break? - Kyoochul Kim; Suk Lee (Korea Development Institute (KDI), 2019)
Many agree that the economy of North Korea has changed under the Kim Jong-un regime, but there are often different interpretations as to whether these changes are in line with the continued transformation from the 1990s or they should be seen as a completely separate trend. And the way of understanding the shift varies on which side you stand. In this context, the KDI Review of the North Korean Economy September edition chose "Macroeconomic Trends in the Kim Jong-un Era: Continuation or Break" as the first theme of its new section, 'Dialogue.' The section covers expert interviews devoted to exploring fundamental and diverse research questions about the North Korean economy in the aspects of economics. We hope that readers find this article interesting and informative.
Keywords: 330